Translation of a poem in boundary situation - Ernst Jandl: ottos mops / ottův pooch - Malý, Radek (Bohemica Olomucensia, 2013)
The paper deals with the analysis of most popular poem of Austrian poet Ernst Jandl (1925-2000) ottos mops and tries to enlighten the possibilities of translation of this poem. The experimental poem based on the principle of monovocalism is believed to be very problematic for translators, but nevertheless the poem became very popular in its various translations. The translations are mostly preserving specific language and situation humour of the poem, but in the same way they are depriving the poem in the area of its deeper sense and meaning. Deeper meaning of the poem was pointed out by E. Jandl and by his colleague, writer Friederike Mayröcker. As the author of the paper states, Czech translator B. Grögerová was succesful in her translation of the poem because she integrated the extratextual means in the translation.